1998
DOI: 10.1016/s0920-9964(98)00069-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical aspects of motor and perceptual processes in schizophrenic patients and healthy controls

Abstract: The present study examined the temporal stationarity of the performance of 16 schizophrenic patients and 16 controls matched for age and sex in a bimanual coordination task and a perceptual task. In the motor task, rhythmic finger oscillations (alternating activity of homologue muscle groups) at increasing speed levels resulted in two measures, the preferred oscillation frequency and the critical frequency at which phase transitions (change towards simultaneous activity of homologue muscle groups) occurred. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…According to previous research showing higher coherent motion thresholds and aberrant processing of second order motion stimuli in ASD (Bertone et al 2003;Milne et al 2002;Pellicano et al 2005;Spencer et al 2000;Spencer and O'Brien 2006), we hypothesized that our patient group would perceive the coherent pattern motion for a shorter amount of time as compared to the control group. In addition, we looked at the rivalry rate of the bi-stable percept as it has been suggested that the rivalry rate reflects the stability of perceptual processes (Keil et al 1998). Our data did not reveal any differences between the subjects with ASD and the control subjects on either measure.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…According to previous research showing higher coherent motion thresholds and aberrant processing of second order motion stimuli in ASD (Bertone et al 2003;Milne et al 2002;Pellicano et al 2005;Spencer et al 2000;Spencer and O'Brien 2006), we hypothesized that our patient group would perceive the coherent pattern motion for a shorter amount of time as compared to the control group. In addition, we looked at the rivalry rate of the bi-stable percept as it has been suggested that the rivalry rate reflects the stability of perceptual processes (Keil et al 1998). Our data did not reveal any differences between the subjects with ASD and the control subjects on either measure.…”
Section: Discussionmentioning
confidence: 68%
“…To test this we exposed our subjects to two different plaids, each leading to different degrees of coherent motion perception. Finally, it has been shown that in schizophrenia and bipolar disorder, perceptual rivalry rates (i.e., the frequency of alternations) are, respectively, higher and lower compared to those of control subjects (Keil et al 1998;Miller et al 2003). According to Keil et al rivalry rate patterns reflect the stability of perceptual processes, suggesting lower stability of visual processing in schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…For example, both Hunt & Guilford (1933) and Philip (1953) report that subjects with paranoid schizophrenia have rivalry rates between those of BD subjects and non-paranoid schizophrenics, though this is not consistent with the data of Keil et al (1998) in which nearly all subjects studied had paranoid schizophrenia and rivalry rates were not significantly different from controls.…”
Section: Rivalry Rates In Other Psychiatric Disordersmentioning
confidence: 70%
“…Parahippocampal neurons may provide some of the directional information that healthy volunteers obtain from the middle temporal system. Future studies should provide a clearer picture of how this diagnostic group relies on alternative systems for perceptual and motor skill acquisition (Mather and Putchat, 1984;Schröder et al, 1995;Schwartz et al, 1996;Keil et al, 1998;Schröder et al, 1999;Weickert et al, 2002;Exner et al, 2006). To what extent does activity in a "secondary" system result in diminished skill acquisition?…”
Section: A1 To A2 Late Learning Pattern Changesmentioning
confidence: 99%